EP709 Segmental ureteral resection with ureteroneocystostomy for gynecologic malignances: a case series. (1st November 2019) - Federico, A; Foschi, N; Conte, C; Gallotta, V; Ferrandina, MG; Pinto, F; Bruno, M; Scambia, G; Bassi, P; Zattoni, F; Vizzielli, G
Abstract : Introduction/Background: Primary or recurrent gynecological cancers involving low urinary tract may require demolitive surgery with curative purpose. We aim to assess surgical outcomes in patients undergoing segmental ureteral resection with ureteroneocystostomy as part of surgical procedures in advanced or recurrent gynecological cancers. Methodology: We retrospectively evaluated post-operative data of all gynecological cancer patients consecutively referred to our Center between March 2012 and July 2018, who underwent unilateral ureteral resection and ureteroneocistostomy with or without psoas-bladder hitch (PBH), in case of macroscopic evidence of ureteral infiltration to achieve oncological radicality. Results: A total of forty-six patients underwent surgery, including seventeen (37%) locally advanced cervical cancer, nine (19.5%) ovarian cancer recurrence, eight (17.4%) ovarian cancer, twelve (26%) other gynecological malignancies. Twenty-two patients (47.8%) experienced at least one high-grade post-operative complication and fourteen patients (30.4%) had major urological complications. Four patients (8.7%) died of complications within 90 days from surgery. Nine (69.2%) of thirteen patients with personal history of pelvic irradiation, had major urological complications, whereas only five (15.2%) among the thirty-three patients with negative history of pelvic irradiation experienced such type of complication. At multivariate analysis pre-operative radiotherapy (p=0.046) and history of pelvic irradiation (p=0.021) were independently associated with an increased risk of developing severe urinary complications. Age, peritoneal carcinosis and prolonged operative time did not correlate with an increased rate of such complications. Conclusion: In gynecologic oncologic surgery, ureteral resection with ureteroneocystostomy has high rate of related morbidity and mortality. Previous pelvic irradiation is strongly associated with severe urological complications. Disclosure: Nothing to disclose.